Gender dimensions of sweetpotato production and consumption in Rwanda - International Potato Center (2013)
The Rwanda Super Foods Project seeks to assess the relative e!ciency of sweetpotato product value chains and their potential to increase farmer income and equity. Since the crop is largely grown by women farmers in Rwanda, the project investigates whether an improved sweetpotato value chain can improve women’s income and empowerment. In many countries, when a crop is commercialized, men become more involved in its production and sometimes dominate the income earned from sales.